2013
DOI: 10.3748/wjg.v19.i48.9318
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a hydroxynaphthoquinone fraction fromArnebia euchromain rats with experimental colitis

Abstract: These findings suggest that HM possesses favourable therapeutic action in TNBS-induced colitis, which provides direct pharmacological evidence for its clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The anti-inflammatory effects of natural naphthoquinones have been extensively investigated. For instance, Fan et al (2013) investigated the effectiveness of hydroxynaphthoquinone mixture (HM) isolated from A. euchroma in rats with experimental colitis induced by 2, 4, 6-tri-nitrobenzene sulfonic acid (TNBS) in 2013. Their results suggested that HM can remarkably attenuate the clinical and histopathological severity of the TNBS-induced colitis in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The anti-inflammatory effects of natural naphthoquinones have been extensively investigated. For instance, Fan et al (2013) investigated the effectiveness of hydroxynaphthoquinone mixture (HM) isolated from A. euchroma in rats with experimental colitis induced by 2, 4, 6-tri-nitrobenzene sulfonic acid (TNBS) in 2013. Their results suggested that HM can remarkably attenuate the clinical and histopathological severity of the TNBS-induced colitis in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Small sections of colonic tissue were fixed in 10% buffered formalin and embedded in paraffin. Thereafter, the sections were stained with haematoxylin and eosin (H&E) and the colonic mucosa was histologically evaluated by a pathologist in a blinded fashion, which was widely used as evaluation criterion ( Fan et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxynaphthoquinones (alkannin and shikonin) are the active components of this traditional medicine that have anti-inflammatory, anti-bacterial, anti-fungal, and immune-modulatory roles. [101112] AE was a safe medication used to improve wound healing in burn victims in some studies. [10] The histologic evaluation of the wounds of the rats treated by AE ointment showed that it has improving effects on blood vessels and their density, fibroblast formation, granulation tissue formation, and collagen bundle synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[10] The histologic evaluation of the wounds of the rats treated by AE ointment showed that it has improving effects on blood vessels and their density, fibroblast formation, granulation tissue formation, and collagen bundle synthesis. [11] Based on the positive findings of AE, we designed a double-blind single-center clinical trial to investigate the effectiveness of AE ointment on AC and AF.…”
Section: Introductionmentioning
confidence: 99%